(3GdYOO GdeYJHQ aj GdChLg Hjf GdShQs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s
(3ChdgG (B:s
(3hHYO aHYV ef jbQC Ydj cGf SCdfj Yf HYV GdChLg Hjf GdShQ aCLHJg HeG CQLh Gf jchf gh GdUhGH s
(3BNQgG (B:s
(3hgj efOQLI eY bGdhf GdHRj SHY eGFI hLg hKeGfjI hSJhf hLgkG hCQHYI hKeGfhf hLgkG hHRjGOI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B270s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B96s
Keywords: (3GdbQGAGJ hGdJLhjOs